1976
DOI: 10.1111/j.1365-2672.1976.tb04161.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Plant Growth Regulators by Rhizosphere Phosphate‐solubilizing Bacteria

Abstract: Culture supernatant fluids of 50 phosphate‐dissolving bacteria isolated from rhizospheres of crop plants were examined for IAA, gibberellins and cytokinins. These bacteria possessed phytase activity and 27 could dissolve rock phosphate. Twenty bacteria synthesized all 3 types of plant hormones, 43 produced IAA, 29 formed gibberellins and 45 cultures produced cytokinin‐like substances. Of the 50 bacteria tested 28 decomposed IAA. Plant growth inhibitors were detected in cultures of some isolates. The ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
5

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(68 citation statements)
references
References 17 publications
4
59
0
5
Order By: Relevance
“…The production of plant growth-regulators by many bacterial species and their effect on plant growth was reported more than 30 years ago (Barea et al 1976). Microbial inoculants, such as PGPR, can alter root architecture and promote plant development via the production or degradation of the major groups of plant hormones (Bhattacharyya and Jha 2012;Dodd et al 2010;Idris et al 2007).…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 99%
“…The production of plant growth-regulators by many bacterial species and their effect on plant growth was reported more than 30 years ago (Barea et al 1976). Microbial inoculants, such as PGPR, can alter root architecture and promote plant development via the production or degradation of the major groups of plant hormones (Bhattacharyya and Jha 2012;Dodd et al 2010;Idris et al 2007).…”
Section: Plant Growth Promotion Resulting From Better Nutrient Uptakementioning
confidence: 99%
“…Barea et al (1976) reported that among 50 bacterial isolates obtained from the rhizosphere of various plants, 86, 58 and 90% isolates produced auxins, gibberellins and kinetin-like substances, respectively. The production of phytohormones has also been reported in other PGPR strains including Azotobacter chroococcum (Muller et al, 1989), Azospirillum spp.…”
Section: Fifty Five Bacterial Isolates Representingmentioning
confidence: 99%
“…조절인자인 식물호르몬 (phytohormone)을 생산함에 따라 나 타나며 식물성장 관련 식물 호르몬들로는 auxin, gibberellin, cytokinin 등이 알려져 있다 (Barea et al, 1976;Glick, 1995).…”
Section: 이와 같은 Pgpr 세균의 식물성장촉진 기능은 식물생육unclassified